2012
DOI: 10.1016/j.enbuild.2012.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the cooling capacity of a radiant cooled ceiling system

Abstract: Nowadays, radiant ceiling systems can be considered among the technologies capable of meeting sustainable heating and cooling requirements. In order to adequately address design and simulation issues concerning these systems, correct evaluation of the heat transfer process is needed. The aim of this research is to present further evidence on the cooling capacity and heat transfer coefficients for a cooled radiant ceiling, assuring adequate thermal comfort levels in those possible different operation conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Jeong and Mumma studied the benefits of such a system, and demonstrated that the system reduced energy usage by 42% compared to a standard VAV system [9] and also studied the cooling capacity of metal ceiling panels similar to what we implemented in the BubbleZERO [11]. Also there have been detailed experimental studies of the heat transfer from radiant panels into building spaces [12,13].…”
Section: High Temperature Radiant Coolingmentioning
confidence: 99%
“…Jeong and Mumma studied the benefits of such a system, and demonstrated that the system reduced energy usage by 42% compared to a standard VAV system [9] and also studied the cooling capacity of metal ceiling panels similar to what we implemented in the BubbleZERO [11]. Also there have been detailed experimental studies of the heat transfer from radiant panels into building spaces [12,13].…”
Section: High Temperature Radiant Coolingmentioning
confidence: 99%
“…Surface heat transfer can be calculated either separately for convection and radiation, as is the case in Chapter 6 of ASHRAE Handbook, HVAC Systems and Equipment [13] and recommended by researchers [14] or can be characterized using a combined heat transfer coefficient as is recommended by ISO 11855(2012). Usually, scientists are interested in the first approach, while designers prefer to use a combined heat transfer coefficient [15].…”
Section: Heat Transfer At the Radiant Surfacementioning
confidence: 99%
“…It can be integrated into the floor, wall or ceiling structure as the so-called thermally activated building system (TABS), or installed as a part of a suspended floor or ceiling. The thermal comfort and energy consumption of radiant surfaces have been an important topic of several studies described in the literature [4][5][6][7][8][9][10][11][12][13][14]. These studies are mainly based on small-scale experiments or numerical models, and they focus on rather specific questions about radiant ceiling systems.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bonacci study, this could refer more to temperature fluctuations and extreme outdoor temperatures in certain periods of time than to general linear trends of yearly mean increase in air temperature [3]. Large-surface radiant systems have recently become a good alternative for heating and cooling the indoor built environment [4][5]. This technology efficiently uses the principle of small temperature difference between a large radiant surface and its surroundings [5].…”
Section: Introductionmentioning
confidence: 99%